Application of higher order Haar wavelet method for solving nonlinear evolution equations - Ratas, Mart; Salupere, Andrus (Mathematical Modelling and Analysis, 2020)
The recently introduced higher order Haar wavelet method is treated for solving evolution equations. The wave equation, the Burgers’ equations and the Korteweg-de Vries equation are considered as model problems. The detailed analysis of the accuracy of the Haar wavelet method and the higher order Haar wavelet method is performed. The obtained results are validated against the exact solutions.